The Coordination of the Integrated Development between Sports Tourism Industry Standardisation and Tourism Urbanisation - Xiaomei Li; Xue Qi; Junyue Yang (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
With the growing demand for sports and tourism among urban residents and the support of national policies, an important topic for urgent research is to explore the integrated development mechanism between sports tourism industry agglomeration standardisation and tourism urbanisation. There is a lack of research on the virtuous integrated and coordinated development mechanism between the two. In response, this paper conducts a study on the coordination of the integrated development between sports tourism industry standardisation and tourism urbanisation. The paper elaborates on the development model of sports tourism industry, and presents a systemic causal loop of their integrated development. It delivers a spatio-temporal relationship analysis on whether there is sustainable integrated interaction between the two and accordingly constructs a spatio-temporal analysis model. Based on Pearson correlation coefficient, cluster analysis and coupling coordination degree, the paper conducts a quantitative analysis to further explore the interaction mechanism between the two, and gives a calculation method for the coordination of their integrated development. At last, the paper compared the comprehensive development levels of sports tourism industry standardization and tourism urbanization, gave the measurement and calculation results of the level of their integrated development, and verified the effectiveness of the proposed research method. This study has certain significance for improving the correlation between sports tourism industry standardization and tourism urbanization in the urban research system.